2009
DOI: 10.1016/j.pnpbp.2009.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Different sub-anesthetic doses of ketamine increase oxidative stress in the brain of rats

Abstract: Schizophrenia is a complex neuropsychiatric disorder in which symptoms can be classified as either positive, such as delusions and hallucinations, or negative, such as blunted affect and social withdrawal. However, the mechanisms underlying this disease are poorly understood. There is evidence that reactive oxygen species (ROS) play an important role in the pathogenesis of many diseases, particularly those which are neurological and psychiatric in nature. Ketamine has been used to induce a schizophrenia-like c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 33 publications
6
48
2
Order By: Relevance
“…Basically, the ketamine-induced NOX2 activation could be either a direct consequence of NMDA receptor inhibition or attributable to another pathway. The fact that two NMDA receptor antagonists, ketamine and dizocilpine [(ϩ)-5-methyl-10,11-dihydro-5H-dibenzo [a,d] cyclohepten-5,10-imine maleate], both induce cerebral ROS generation during injection in rats (de Oliveira et al, 2009) and mice (Zuo et al, 2007) support the former possibility. However, given the lack of cellular studies specifically addressing this issue, it is, at this point, difficult to exclude that ketamine activates NOX2 through other mechanisms.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Basically, the ketamine-induced NOX2 activation could be either a direct consequence of NMDA receptor inhibition or attributable to another pathway. The fact that two NMDA receptor antagonists, ketamine and dizocilpine [(ϩ)-5-methyl-10,11-dihydro-5H-dibenzo [a,d] cyclohepten-5,10-imine maleate], both induce cerebral ROS generation during injection in rats (de Oliveira et al, 2009) and mice (Zuo et al, 2007) support the former possibility. However, given the lack of cellular studies specifically addressing this issue, it is, at this point, difficult to exclude that ketamine activates NOX2 through other mechanisms.…”
Section: Discussionmentioning
confidence: 87%
“…Ketamine administration causes an increase in ROS production (Zuo et al, 2007) and oxidative damage (de Oliveira et al, 2009) in the brain. However, the source of the ROS generation is not known.…”
Section: Stress-related Markers After Ketamine Injectionmentioning
confidence: 99%
“…Also, increased levels of markers for lipid per oxidation were observed in a similar population (Dadheech et al, 2008;Padurariu et al, 2010). Additionally, a study performed by our group suggested that the animal model of schizophrenia induced by ketamine showed changes in the activity of superoxide dismutase (SOD), catalase (CAT) and GPx, resulting in protein and lipid damage (De Oliveira et al, 2009). …”
Section: Introductionmentioning
confidence: 85%
“…#SOD (cerebellum, prefrontal cortex, hippocampus) #CAT (cerebellum, prefrontal cortex, hippocampus) [126] G72/G30 transgenic schizophrenia mice " lipid peroxidation (brain) #GSH (brain) [128] G72/G30 transgenic schizophrenia mice -#CAT (cerebellum) [131] Social isolation/Ppp1r2-Cre/ fGluN1 knockout mice " ROS production (medial prefrontal cortex, S1 cortex)…”
Section: Clinical Studiesmentioning
confidence: 99%